Is Probiotic an Alternative to Systemic Antibiotics in treating Chronic Periodontitis? - Sana Ikram, Nuzhat Hassan, Saeeda Baig, Jaimala Kishore, Zohaib Ahmed, Muhammad Arsalan Raffat (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: to assess the clinical efficacy of three treatment modalities (Lactobacillusreuteri (L. reuteri) + Scaling and root planning (SRP), broad spectrum antibiotics+ SRP and SRP alone) and to compare their efficacy in the treatment of Chronic periodontitis. Methods: Sixty systemically healthy participants (20 Group A, 20 Group B and 20 Group C), clinically diagnosed with CP were enrolled. All patients underwent SRP. Adjunctive Amoxicillin and metronidazole were given thrice and twice daily respectively for 7 days to the Group A participants. Adjunctive probiotic wasgiven twice daily for 3 months to the Group B participants whereas, no adjunctive was provided to the participants of Group C. Results: Statistically significant improvement was observed in the participants of each group A, B and C for every clinical parameter i.e., plaque index (PI), bleeding on probing (BOP), periodontal pocket depth (PPD) and clinical attachment level (CAL) gain on each follow-up visit. However, Group A and Group B exhibited superior results than Group C. Conclusion: Treatment of CP with SRP along with adjunctive modalities improves clinical periodontal outcomes as compared to SRP alone. However, two adjunctive modalities i.e., systemic antibiotics and L. reuteri are comparable in efficacy. Keywords: chronic periodontitis; probiotics; lactobacillus reuteri; dental scaling; antibiotics